2015
DOI: 10.1590/1414-431x20144100
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of etomidate-induced myoclonus during anesthetic induction by pretreatment with dexmedetomidine

Abstract: Myoclonus induced by etomidate during induction of general anesthesia is undesirable. This study evaluated the effect of dexmedetomidine (DEX) pretreatment on the incidence and severity of etomidate-induced myoclonus. Ninety patients undergoing elective surgical procedures were randomly allocated to three groups (n=30 each) for intravenous administration of 10 mL isotonic saline (group I), 0.5 µg/kg DEX in 10 mL isotonic saline (group II), or 1.0 µg/kg DEX in 10 mL isotonic saline (group III) over 10 min. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 24 publications
(27 reference statements)
6
30
0
Order By: Relevance
“…Yang X et al 16 also showed a reduction in the etomidate induced myoclonus in lidocaine group when compared with placebo. In the present study, the incidence of myoclonus at one and two minutes with 68% and 64% respectively in the control group and 30% and 38% respectively in the lidocaine group was observed which was in accordance with the findings of Luan HF at al 17 who reported an incidence of etomidate induced myoclonus of 63.3% at one minute with normal saline. Lang B et al 15 reported that there was a significant difference between the lidocaine group and the saline group in the incidence of etomidate induced mild myoclonus (13% with lidocaine versus 21.1% with saline) comparable with the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Yang X et al 16 also showed a reduction in the etomidate induced myoclonus in lidocaine group when compared with placebo. In the present study, the incidence of myoclonus at one and two minutes with 68% and 64% respectively in the control group and 30% and 38% respectively in the lidocaine group was observed which was in accordance with the findings of Luan HF at al 17 who reported an incidence of etomidate induced myoclonus of 63.3% at one minute with normal saline. Lang B et al 15 reported that there was a significant difference between the lidocaine group and the saline group in the incidence of etomidate induced mild myoclonus (13% with lidocaine versus 21.1% with saline) comparable with the present study.…”
Section: Discussionsupporting
confidence: 92%
“…10 It can be of a concern in full stomach patients, in penetrating eye injuries, high intraocular pressure. Ko B 11 et al studied the incidence of myoclonus after etomidate induction using fentanyl and remifentanil as premedicants.…”
Section: Myoclonusmentioning
confidence: 99%
“…When etomidate was first introduced in 1973, it was known as an agent with hypnotic properties that possessed minimal cardiovascular and pulmonary complications (1). Etomidate maintains hemodynamic stability and eliminates histamine release more profoundly than other drugs (2).…”
Section: Introductionmentioning
confidence: 99%
“…Myoclonus can be detrimental to full-stomach patients undergoing emergency surgery, patients with an open eye injury, and those with a history of cardiovascular disease (2,6). Although the mechanism of myoclonus is not fully understood, various medications have been used to prevent the occurrence of myoclonus (1), including fentanyl (2), benzodiazepines (7), rocuronium (8), opioids (9), Copyright © 2019, Author(s). This is an open-access article distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 International License (http://creativecommons.org/licenses/by-nc/4.0/) which permits copy and redistribute the material just in noncommercial usages, provided the original work is properly cited.…”
Section: Introductionmentioning
confidence: 99%